Challenges faced by Islamic and non-Islamic institutions in offering microtakaful and microinsurance products in Malaysia / Nur Syuhadah Abdul Khalid - Abdul Khalid, Nur Syuhadah (Faculty of Business and Management, 2015)
Microtakaful and microinsurance fit into the product category for the low income and poor. This product is to empower people in seeking a way out of their poverty and to give them hope of being financially self-sustainable. However, it is not easy for the insurance and takaful institutions to provide this products to the low income and poor due to several reasons. The purpose of this study is to identify whether those factors which are awareness level, availability of expertise in insurance sector, moral hazard and also affordability of the poor will give challenges to the Islamic and non-Islamic insurance institutions in offering microtakaful and microinsurance products in Malaysia. The study was conducted among staff of insurance and takaful institutions in Kuala Lumpur and Selangor. It was found that all the independent variables have associate relationships with the challenges in offering these products. The researcher recommends that intervention and support from government is vital in providing the financial capacity for the poor to have the needed protection that principally cover death, medical and savings benefits. Besides that, government and insurance institutions should aggressively promote microtakaful and microinsurance products to increase the awareness level and to have better understanding on the importance of having insurance protection.